EFEKTIVITAS TEKNIK CINEMATHERAPY UNTUK MENGURANGI KECEMASAN - SA`ADAH SA`ADAH; SULMA MAFIRJA (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2019)
The purpose of this study was to look at the effectiveness of cinematherapy techniques to reduce student anxiety in Angsana 1 High School. This type of research is a single subject research or called Single Subject Research (SSR) on the subject of class XI students in SMA Negeri 1 Angsana. Study design A1-B-A2. The results showed a significant increase in interpersonal communication through brainstorming techniques at baseline A1, intervention, and baseline A2.